Hubungan Olahraga dengan Kesehatan Mental - Javier Nayaka Airlangga; Akhmad Syarif; Muhammad Abdul Wahid Syawali; Sri Mulyeni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Exercise is a planned physical activity that not only contributes to physical fitness but also plays a significant role in maintaining and improving mental health. This study aims to explore the relationship between physical exercise and mental well-being among adolescents and university students with diverse backgrounds of physical activity. The research employs a qualitative approach using in-depth interviews with five informants, consisting of university students who engage in recreational exercise, recreational runners, middle- and long-distance runners, and a sprinter. Data collection was conducted in several public sports spaces in the city of Bandung, focusing on participants’ subjective experiences related to their psychological conditions before and after engaging in exercise. The findings indicate that all participants perceive exercise as an effective means of emotional regulation. Physical activity is consistently associated with improved mood, reduced stress, enhanced sleep quality, stable energy levels, and increased academic concentration and focus. In addition, exercise contributes to the development of self-confidence, self-efficacy, and self-control through structured routines. The social aspects of exercise, such as support from peers, communities, and coaches, were shown to strengthen the sustainability of physical activity while also providing essential emotional support for mental health. However, among competitive athletes, performance-related pressure was identified as a factor that may negatively affect psychological well-being, although this effect can be moderated by adequate social support. Overall, the findings of this study emphasize that exercise functions as an adaptive coping mechanism operating through biological, psychological, and social pathways, and highlight the importance of consistency and balance in physical activity to achieve optimal mental health benefits.